Konsep á¹¬ÄgÅ«t Pada Anak Usia Dini Dalam Kitab TaÊ»lim al-á¹¢ibyÄn al-Tawá¸¥Ä«d - Sam, Sugiyanto; Suhra, Sarifa (Institut Agama Islam Negeri (IAIN) Bone, 2024)
The lesson á¹¬ÄgÅ«t from the book TaÊ»lim al-á¹¢ibyÄn al-Tawá¸¥Ä«d is explained in this article. The kind of research used in this investigation is library research (library research). The methods that are applied are historical, theological, and pedagogical. Documentary study is the method used in this research to acquire data. To examine the data that has been gathered, researchers employ content analysis techniques, or content analysis. According to the study's findings, the topic of á¹¬ÄgÅ«t in the book TaÊ»lim al-á¹¢ibyÄn al-Tawá¸¥Ä«d is meant to teach kids about religion and to help them understand that they should avoid making any sacrifices other than to Allah because doing so can undermine confidence in Allah. This book uses the question and answer format as its teaching style. The findings of this study indicate that the lesson on á¹¬ÄgÅ«t in early life from the book TaÊ»lim al-á¹¢ibyÄn al-Tawá¸¥Ä«d aims to teach children about á¹¬ÄgÅ«t from an early age, which can harm a Muslim's faith. Children will be able to comprehend that Allah is the only one deserving of worship and obedience, and that all other sources of authority or power are merely temporary and relative. Children who comprehend this idea may grow to be critical of the harmful effects in their environment, such as excessive consumerism, social injustice, or even fanaticism toward particular individuals or ideologies.Keywords: á¹¬ÄgÅ«t, Children's Education, TaÊ»lim al-á¹¢ibyÄn al-Tawá¸¥Ä«d